Environmental Protests and Constitutional Protection of Political Communication: Brown v Tasmania. (10th May 2018) - Edgar, Andrew
ABSTRACT: Australian state Parliaments have recently enacted legislation responding to direct action protests in which protesters have disrupted forestry and mining activities by blocking roads, building tree houses, and locking themselves to machinery and structures. The High Court of Australia, in Brown v Tasmania [2017] HCA 43 considered a challenge to one of these Acts, the Workplaces (Protection from Protesters) Act 2014 (Tas), and determined that its primary provisions were invalid in their application to forestry land for being in breach of the constitutional freedom of political communication. This analysis piece examines Brown v Tasmania by reference to two features of its context: the direct action protests that prompted the Tasmanian Parliament to enact this legislation and the documentary activism that occurred on the facts of Brown v Tasmania . It highlights that broad and uncertain protest laws risk being characterised as insufficiently adapted to the protection of political communication in Australian constitutional law.